The Influences of Audio Visual Media And Vocabulary Mastery towards English Learning Achievement of EFL Students - Tubagus Zam Zam Al Arif (UIR Press, 2020)
This study was an attempt to determine the impact of interaction between teaching media and vocabulary mastery towards students’ learning achievement in colleges of education at Jambi University. This is a quasi-experimental study with nonequivalent control and experimental group design. Based on the test for normality, homogeneity, and analysis of variance to the data students’ achievement score of experiment class can be concluded that, there are significant differences of learners’ achievement between before and after treatment in experimental class using audio-visual media. Then, there are significant differences between the learners’ vocabulary mastery on their learning achievement. The result of this study showed; 1. There is a significant effect between teaching media toward learners’ achievement. Test result obtained that p-value 0,015 (<0,05) 2. Vocabulary mastery gave the significant effect to the learners’ achievement. Test result obtained that p-value for vocabulary mastery is 0,000 (<0,05). 3. There is no interaction influence between the teaching media and vocabulary mastery towards learners’ achievement. Test result retrieved that p-value is 0,948 (>0,05).